STRENGTHENING STUDENTS' RELIGIOUS CHARACTER THROUGH RELIGIOUS PRACTICES IN ELEMENTARY SCHOOL - Laurita Nurmila Arinda; Muhlasin Amrullah; Khizanatul Hikmah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper examines the strengthening of students' religious character education through religious practices at Al-Islam Plus Krian Elementary School. The research employs a qualitative approach with a phenomenological design. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion techniques. Data validity was ensured through source and technique triangulation. The study identifies various religious activities that strengthen students’ character, including the 7S culture, praying before and after learning, reciting hadiths and daily prayers, Quran recitation, reading Asmaul Husna, istighosah, congregational prayers (Duha, Zuhr, Asar, Friday), tarjamah, tahfidz Al-Qur’an, and PHBI activities. The findings indicate that these religious practices have a significant impact on students, enhancing their understanding of positive behaviors and encouraging them to apply these practices in their daily lives according to Islamic Shariah principles.